Peran IT Manager di Perusahaan Modern - Andri Firmansyah (Teknik Informatika, Universitas Pelita Bangsa, 2021)
IT Manager can be likened to a person who has a lot of hats. Various parts of the organization will have different expectations towards you, and you should be able to meet these expectations. Part finance hope you are able to handle the financial affairs; Sales and Marketing wants to see you shine in assisting the acquisition of the company's revenue; Your staff need guidance and career development; while the administrative staff hopes its flagship printer does not crash if used to complete the task. An IT Manager today to have a different role to the past 10-20 years that are primarily dealt only glass house (data center). IT Manager responsibilities now include data centers, telecommunications, IT staff take care of, websites, user support, disaster recovery, compliance to user support. This is good news and bad news at the same time. At some companies, IT Manager will play a direct role and participate in determining the company's strategic planning Keywords: role, IT Manager, companies